Progress and Confusion : The State of Macroeconomic Policy. (International Monetary Fund, 2016)
Leading economists consider the shape and future of economic policy: Will it resume the pre-crisis consensus or contend with the post-crisis 'new normal'? Have we made progress with addressing the major issues or does confusion remain in today's economic environment? Chapters address topics that range from the measurement of systemic risk to foreign exchange intervention.